Psychometric properties of a brief self‐reported health‐related quality of life measure (HRQoL‐IDD) for persons with intellectual and developmental disabilities. Issue 3 (31st January 2021) - Pett, Marjorie A.; Guo, Jia‐Wen; Cardell, Beth; Johnson, Erin P.; Guerra, Nichole; Clark, Lauren
Abstract: Background: To encourage self‐determination and address health disparities among persons with intellectual and developmental disabilities, clinicians and researchers rely on self‐reported measures like health‐related quality of life (HRQoL). This study evaluated the psychometric properties of a theory‐driven self‐reported HRQoL measure for adults requiring mild to moderate support related to intellectual and developmental disabilities. Method: 224 volunteers completed 42 quality of life items developed with extensive input from persons with intellectual and developmental disabilities, family members/caregivers, and providers. The 5‐point Likert scale format with visual images of fluid‐filled cups represented the range of responses. Results: Exploratory and Unrestricted Factor Analyses yielded 16 HRQoL items with 4 subscales: Functional Well ‐ Being, Emotional Well ‐ Being, Social Well ‐ Being, and Healthy Decision‐making . The HRQoL‐IDD explained 62.8% of variance, had satisfactory internal consistency (0.73–0.83), stability of reponses, and reading level (2nd grade, ages 7‐8). Conclusions: The HRQoL‐IDD is a promising measure of self‐reported HRQoL for use in community‐based settings for persons requiring mild to moderate support related to intellectual and developmental disabilities.